Development and Testing of Screen-Based and Psychometric Instruments for Assessing Resident Performance in an Operating Room Simulator - Richard R. McNeer; Roman Dudaryk; Nicholas B. Nedeff; Christopher L. Bennett (Anesthesiology Research and Practice)
Introduction. Medical simulators are used for assessing clinical skills and increasingly for testing hypotheses. We developed and tested an approach for assessing performance in anesthesia residents using screen-based simulation that ensures expert raters remain blinded to subject identity and experimental condition. Methods. Twenty anesthesia residents managed emergencies in an operating room simulator by logging actions through a custom graphical user interface. Two expert raters rated performance based on these entries using custom Global Rating Scale (GRS) and Crisis Management Checklist (CMC) instruments. Interrater reliability was measured by calculating intraclass correlation coefficients (ICC), and internal consistency of the instruments was assessed with Cronbach’s alpha. Agreement between GRS and CMC was measured using Spearman rank correlation (SRC). Results. Interrater agreement (GRS: ICC = 0.825, CMC: ICC = 0.878) and internal consistency (GRS: alpha = 0.838, CMC: alpha = 0.886) were good for both instruments. Subscale analysis indicated that several instrument items can be discarded. GRS and CMC scores were highly correlated (SRC = 0.948). Conclusions. In this pilot study, we demonstrated that screen-based simulation can allow blinded assessment of performance. GRS and CMC instruments demonstrated good rater agreement and internal consistency. We plan to further test construct validity of our instruments by measuring performance in our simulator as a function of training level.